Integrated multiscale design for emulsion formulations : novel optimization scheme and experimental validation (2018)
This work is divided into two articles in which an integrated multiscale design is prosed through the combination of experimental methodologies and computational techniques for emulsion formulations. The first article presents an optimization proposal for the emulsion formulations considering a multiscale approach. This proposal is based on the integration of mathematical model which describe molecular, microscopic and macroscopic properties along with consumer preferences and economic considerations. Through the optimization proposal, the optimal formulations are obtained and so it is possible to reduce the time and resource spent on experimental product design methodologies. In the second article, a validation and subsequent adjustment of the properties obtained in the formulation given by the optimization proposal is carried out. This study is based on the comparison of microscopic and macroscopic properties achieved by the optimization model and experimental data. This experimental validation was quite favorable since the limitations of the optimization proposal were understood through the relation between the multiscale properties, which allows modifications to the mathematical models in order to define the molecular, microscopic and macroscopic structure of emulsions precisely.